RETRACTED: Socio-demographic factors of the employed population digital skills development - Gurieva Lira; Baburina Olga; Dzhioev Aleksandr (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001